2011
DOI: 10.5688/ajpe756112
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diabetes Concentration Programs on Pharmacy Graduates' Provision of Diabetes Care Services

Abstract: Objective. To determine practice outcomes associated with doctor of pharmacy (PharmD) graduates from 2 universities who completed a diabetes-concentration.Methods. An online survey instrument was sent to 93 PharmD graduates who completed a concentration in diabetes and 94 control graduates to determine their knowledge of and skills in providing diabetes care and how frequently they provided diabetes care services. Results. Ninety-seven graduates (52%) responded. Significantly more graduates with a diabetes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The pharmacist is the professional with greatest accessibility to patients and this contact may contribute to their care 13,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacist is the professional with greatest accessibility to patients and this contact may contribute to their care 13,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are in a favorable position to systematically identify patients with diabetes, assess the risk of associated comorbidities and assist in disease management and preventive measures 11 . Some studies have shown that outpatient diabetes care pharmaceutical services help improve glycemic control and achieve desired therapeutic goals, [11][12][13][14][15] however, few national randomized controlled trials have verified the effects of pharmacotherapeutic follow-up on the management of patients with diabetes 8,[16][17][18] . Meta-analysis that included 2,961 patients receiving pharmacist care intervention (pharmaceutical care, medication review, solving drug-related problem, education on diabetes, among others) and 2,899 receiving the usual care intervention, showed that the pharmacist care improvement the values of HbA1c in patients of both high-income and low-and middle-income countries.…”
mentioning
confidence: 99%
“…Topics for elective concentrations might include research, 9 leadership, 10 academia, 11 or specialized clinical focus areas. 12 These concentrations may involve partnering with other health professions for interprofessional design and delivery. They can also include partnering with experiential education to provide additional venues for students to practice their new skills.…”
Section: Partnering With Students and Providing A Sandbox For Facultymentioning
confidence: 99%
“…10 There are also pharmacy programs with a concentration or certificate in diabetes. 11 In 2009, Peyrot et al 12 wrote that "additional efforts are required to guarantee that all people with diabetes receive the DSME they need." While it is clear that there are currently not enough diabetes educators available and that there are options in place for becoming educated, certified, and/or licensed in the specialty, the following questions remain:…”
Section: Preparation For Diabetes Educatorsmentioning
confidence: 99%